Locked down apps versus the social media ecology: Why do young people and educators disagree on the best delivery platform for digital sexual health entertainment education?. (December 2018) - McKee, Alan; Albury, Kath; Burgess, Jean; Light, Ben; Osman, Kim; Walsh, Anthony
This article reports on focus groups exploring the best way to reach young men with vulgar comedy videos that provide sexual health information. Young people reported that they found the means by which the material was presented – as a locked down app – to be problematic, and that it would better be delivered through social media platforms such as YouTube. This would make it more 'spreadable'. By contrast, adult sex education stakeholders thought the material should be contained within a locked down, stand-alone app – otherwise it might be seen by children who are too young, and/or young people might misunderstand the messages. We argue that the difference in approach represented by these two sets of opinions represents a fundamental stumbling block for attempts to reach young people with digital sexual health materials, which can be understood through the prism of different cultural forms – education versus entertainment.